Graphite Nanosheets Modified with Carboxymethyl Cellulose as Eco-Friendly Corrosion Inhibitor for Low-Carbon Steel in Saline Environments to Support Sustainable Development Goals (SDGs): An Experimental and Bibliometric Study - Mohamed R. Mohssen; Sinan S. Hamdi; Rana A. Anaee; Hussain H. Al-Kayiem (ASEAN Journal for Science and Engineering in Materials, 2026)
Eco-friendly polymeric nanofluids were developed by modifying graphite nanosheets with carboxymethyl cellulose (CMC) to inhibit low-carbon steel corrosion in saline environments. This experimental and bibliometric study combined nanofluid preparation, dispersion assessment, electrochemical testing, surface characterization, and literature mapping to connect material performance with SDGs. The nanocomposite formed a stable dispersion, reduced corrosion activity, and produced an adsorbed protective layer. This protection occurred because CMC provided oxygen-rich functional groups for adsorption, while graphite nanosheets strengthened the chloride barrier. The findings support safer corrosion-control strategies that may reduce toxic inhibitor dependence and improve the durability of steel infrastructure in marine and industrial environments.